2022
DOI: 10.3390/ijms23136980
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapy Using Human Corneal Stromal Stem Cells and Quiescent Keratocytes to Prevent Corneal Scarring after Injury

Abstract: Corneal blindness due to scarring is conventionally treated by corneal transplantation, but the shortage of donor materials has been a major issue affecting the global success of treatment. Pre-clinical and clinical studies have shown that cell-based therapies using either corneal stromal stem cells (CSSC) or corneal stromal keratocytes (CSK) suppress corneal scarring at lower levels. Further treatments or strategies are required to improve the treatment efficacy. This study examined a combined cell-based trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Recently, Jhanji et al reported an approach to combine keratocytes with corneal stromal stem cells (CSSCs) to reduce scarring. [48] This combined therapy appears to replenish corneal transparency-related proteoglycans via keratocytes and control inflammation via CSSCs, thus achieving higher efficacy than a single treatment. Since the combined therapy involves different cell types and depends on the ratio between them, it is more complex to manipulate, which is unfavorable for the repeatability and consistency of the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jhanji et al reported an approach to combine keratocytes with corneal stromal stem cells (CSSCs) to reduce scarring. [48] This combined therapy appears to replenish corneal transparency-related proteoglycans via keratocytes and control inflammation via CSSCs, thus achieving higher efficacy than a single treatment. Since the combined therapy involves different cell types and depends on the ratio between them, it is more complex to manipulate, which is unfavorable for the repeatability and consistency of the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…At the stromal periphery (anterior limbal stroma), the existence of corneal stromal stem cells (CSSCs) represents an adult progenitor population for CSK. Although there is a lack of in situ evidence showing their differentiation to produce CSK inside CSt, different pre-clinical studies have indicated their therapeutic potency to remodel CSt after injury, resulting in stromal regeneration and a recovery of regular lamellar pattern [ 7 , 8 , 9 ].…”
Section: Cornea—structure and Functionsmentioning
confidence: 99%
“…Native CSKs are difficult to expand ex vivo, as they transit to fibroblasts when propagated with serum and growth factors in culture [ 18 , 71 ]. Our laboratory developed a robust method to expand bona fide CSKs ( Figure 4 A) [ 15 ], which specifically (1) produce and deposit stromal collagens, particularly type I collagen; (2) express stromal proteoglycans (such as keratocan, lumican, and decorin) and stromal crystallins (transketolase, aldehyde dehydrogenase 1A1 and 3A1); and (3) become quiescent in a serum-deprived condition and express CD34 and integrins on the cell surface for intercellular communication [ 9 , 15 , 72 ]. Using in vivo mouse and rat corneal stromal injury models (induced by excimer laser-mediated irregular photorefractive keratectomy and mechanical ablation by high-speed Algerbrush burring, respectively), CSKs were intrastromally injected to corneas with pre-existing early corneal haze and opacities.…”
Section: Cell-based Approach For Corneal Wound Healing and Scar Manag...mentioning
confidence: 99%
“…Both groups that received ADASC demonstrated improvement in paracentral scars. Meanwhile, other candidates for cell replacement are being explored, such as corneal stromal SC which have been shown to control inflammation and fibrosis [28,29]; stromal keratocytes which demonstrated ability to recover the native stromal matrix [30]; or a combination of both [31]. Similarly, additional tissue engineering approaches are exploring different scaffolds [32][33][34].…”
Section: Stromamentioning
confidence: 99%